Can Growth Mindset Affirmation be Advantageous for More-knowledgeable Learners? - Noka Setya Maharani; Endah Retnowati; Ellen Lee (Hipotenusa: Journal of Mathematical Society, 2025)
Growth mindset is known as a believe that intelligent can be learned. Learning anxiety might occur due to self-doubt that one has an ability to learn, such as in a complex topic in mathematics. Therefore, it is assumed that a positive affirmation that directs growth-mindset might be used to manage anxieties in learning mathematics. This study was aimed to investigate that beside the worked example might increase extraneous cognitive load for more knowledgeable learners, it might also be possible it affects anxiety. A total of 128 Indonesian junior high school students were randomly placed in four experiment groups by using the 2x2 factorial design (with vs. without growth mindset affirmation) x (worked example vs. problem solving based instruction) to examine the instruction on transfer abilities, cognitive loads, and level of anxieties. Using ANOVA(s), findings support the expertise reversal effect that the worked examples were disadvantageous for more knowledgeable learners. The data reveals that they also experienced significantly higher anxiety during learning compared to the counterparts. Nevertheless, no effects were found in favor of the growth mindset affirmation.